On the Kinematically Admissible Solution Applied to the Theoretical Analysis of Shoving Processes - Trąmpczyński, W.; Jarzębowski, A. (Engineering Transactions, 1991)
The paper concerns a simplified theoretical analysis of such complex soil shoving processes as, for example, the process of moving walls in a way similar to heavy machine tools (e.g. bucket of a loading machine). Assuming the material to be rigid-perfectly plastic with strain behaviour governed by the Coulomb-Mohr yield criterion and associated flow rule, simple kinematically admissible solutions were found. It was shown that, using this technique step by step, it was possible to analyse complex processes and even to find more effective loading paths.